Etnoconhecimento e contribuições das comunidades locais para a conservação da biodiversidade na Reserva da Biosfera da Serra do Espinhaço - Felipe Silveira Leite (2021)
Biosphere Reserves are integrated management models that seek to reconcile objectives of conservation and sustainable use of biodiversity, recognizing the importance of ethnoknowledge and local management. This study seeks to synthesize information about local and traditional communities in the Serra do Espinhaço Biosphere Reserve (RBSE) regarding knowledge, use and management of biodiversity. From this, the contributions of communities to the conservation and sustainable use of biodiversity were analyzed, as well as their struggle processes for territory and natural resources. A systematic review and a survey of gray literature were carried out, using as databases Scopus, Web of Science, ResearchGate, Google Scholar and the page unescodoc.unesco.org. 37 publications were selected. Twenty works cover rural and urban communities, 11 on geraizeiros, six on quilombola communities and three on evergreen flower pickers. No work on the ethnoknowledge of the biodiversity of the other traditional communities of the RBSE, including 13 ethnic groups of native peoples, artisanal fishermen, veredeiros, and people from terreiros was found, which reveals gaps on the subject. Despite the few studies published in the evaluated databases, 808 species of plants and 64 species of wild animals known and used by these communities were registered in the selected works. In general, the practices and knowledge of local and traditional communities indicate the potential for sustainable use of biodiversity as they seek to meet their conservation needs and objectives. These are knowledge and techniques on the classification and use of environments, species, environmental management, fire management, agroecological and agroforestry management, extractivism, as well as regulation and access to common goods. There is relevant knowledge about biodiversity and practices, mainly agroecological, which provide the Reserve with opportunities to maintain the local culture, as well as to conserve and sustainably use biodiversity.